Análise de materiais didáticos de língua inglesa, elaborados por professores em formação inicial, sob a ótica da multimodalidade - Oliveira, Larisse Carvalho de (2021)
Considering the need for adaptation of teachers to different audiences, this thesis proposed to investigate, in a qualitative, explanatory and interpretive way, how multimodality can contribute to the process of developing teaching materials to teach English, through materials produced by senior students of the English-Portuguese Language course, at a university in the region of Cariri, located in the south of the state of Ceará. We intend to show that a work focused on multiliteracies and multimodality approach can provide advances in the training of future teachers and in the way they prepare their work materials. As theoretical bases, we support our assertions from the perspective of multimodality studies, given its versatility in using different modes (images, audios, hyperlinks, texts, etc.) for the formulation of meanings and its concern with understanding these meanings within a social and cultural perspective (KRESS, VAN LEEUWEN, 2006; VAN LEEUWEN, 2005, 2011; UNSWORTH, 2008; NEW LONDON GROUP, 2000). We also seek: (i) to analyze the syllabuses and bibliographies of the disciplines of the aforementioned course, paying attention to the verification of the promotion of studies on multimodality, or not; (ii) investigate freshman students' assertions about multimodality, its uses and its importance, in order to identify the level of exposure to such concepts in their academic training; (iii) to inquire from senior students about the notions of multimodality and multiliteracies, their understanding and visibility throughout the course so that we can base the knowledge of freshmen when compared to those of senior students; (iv) check the understanding of senior students at the end of the workshop, relating their responses to the material produced by them and their initial responses. With regard to the methodological steps, we can indicate: the collection and qualitative analysis of the political pedagogical plan of the course; the application of two analysis instruments, a questionnaire applied to freshman students of the aforementioned course and another applied at the beginning and at the end of the workshop, for senior students; observation, during the production and presentation of materials by the students and the analysis of their final result, enabling us to compare the follow-up of what was undertaken in the workshop and put into practice by the informants. Regarding the results, we found that: (i) the course's students seem not to have had a minimum exposure to multimodal concepts and theories; (ii) freshmen students were able to sketch some definitions of concepts, based on linguistic relations of word formation; (iii) the same happened with the senior students, with little differentiation between the two groups, despite the difference in time of undertaken studies; (iv) the senior students were able to understand and recreate the concepts at the end of the course, and that the theoretical notions, at the time of answering the questionnaire, helped participants to focus on multimodal aspects when analyzing multisemiotic texts. Finally, we emphasize that the most important discussion of this thesis was the training of English language teachers and their ability to prepare teaching materials, contributing to the promotion of studies and research in multiliteracies, multimodality and teacher training.